2012
DOI: 10.1002/chem.201200151
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids of Cationic Sandwich Complexes

Abstract: Simple cationic sandwich complexes that contained alkyl- or halogen substituents provided ionic liquids (ILs) with the bis(perfluoroalkanesulfonyl)imide anion. Ferrocenium- and cobaltocenium ILs [M(C(5)H(4)R(1))(C(5)H(4)R(2))][Tf(2)N] (M=Fe, Co) and arene-ferrocenium ILs [Fe(C(5)H(4)R(1))(C(6)H(5)R(2))][Tf(2)N] were prepared and their physical properties were investigated. A detailed comparison of their thermal properties revealed the effects of molecular symmetry and substituents on their melting points. Thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 72 publications
(36 reference statements)
5
62
0
1
Order By: Relevance
“…However, there are very few reports on electroactive ILs and there is a very narrow array of available structures and given that the design of a new RIL is hindered by a lack of knowledge of their structure-properties relationships [18][19][20][21][22][23][24]. In addition, the current library of RILs almost exclusively contains structures based on the modification of alkylimidazoliums, with some exceptions from reports on ferrocene-functionalized phosphonium IL [14,25] and metallocenium ILs [26,27]. Our group reported on the development of RIL as redox additive in electrolytes for lithium-ion batteries to protect the cathode against overcharging [28,29].…”
Section: Introductionmentioning
confidence: 95%
“…However, there are very few reports on electroactive ILs and there is a very narrow array of available structures and given that the design of a new RIL is hindered by a lack of knowledge of their structure-properties relationships [18][19][20][21][22][23][24]. In addition, the current library of RILs almost exclusively contains structures based on the modification of alkylimidazoliums, with some exceptions from reports on ferrocene-functionalized phosphonium IL [14,25] and metallocenium ILs [26,27]. Our group reported on the development of RIL as redox additive in electrolytes for lithium-ion batteries to protect the cathode against overcharging [28,29].…”
Section: Introductionmentioning
confidence: 95%
“…[8] However, little has been reported on the anion chain dependence of the thermal properties and structures of the ionic liquids with bis(perfluoroalkylsulfonyl)amide anions. [3a, 9, 10] Recently, we reported that alkyl metallocenium salts with bis(perfluoroalkylsulfonyl)amide anions become ionic liquids, [11] whereas the corresponding cobaltocenium salts are solids at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…For rac- [1][PF 6 ], the origin of the high T g /T m ratio is discussed in the following section. 17 6 ] exhibits a phase transition at 70.1 1C (DS = 18.8 J mol À1 K À1 ). Ionic liquids based on cationic sandwich complexes often undergo phase transitions in the solid state.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Therefore, the effects of molecular structure, such as the length of alkyl substituents, on the physical properties of ionic liquids have been extensively investigated. [17][18][19][20][21] We examine herein how substituent branching and chirality affect the thermal properties of organometallic ionic liquids. [4][5][6][7][8][9][10][11] Although most ionic liquids contain organic cations such as imidazolium cations, various metal-containing ionic liquids that exhibit intriguing functionalities have recently been developed.…”
Section: Introductionmentioning
confidence: 99%